Hemostatic potential of recombinant von Willebrand factor and standard or pegylated extended half-life recombinant factor VIII on thrombus formation under high shear flow - Hiroaki Yaoi; Yasuaki Shida; Kenichi Ogiwara; Keiji Nogami (Thrombosis Journal, 2023)
Abstract Background Von Willebrand factor (VWF) and factor VIII (FVIII) complex play a pivotal role in hemostasis. A deficiency or defect of VWF causes von Willebrand disease (VWD). Recombinant (r)VWF product has proved to be effective for hemostatic treatment of VWD, but limited information is available on their role in moderating thrombus formation under flow condition. We aimed to assess thrombus formation in the presence of rVWF combined with rFVIII or pegylated-extended half-life rFVIII (peg-EHL-rFVIII) in VWD whole blood under high shear flow. Methods Perfusion chamber experiments under high shear (2,500 s− 1) combined with immunostaining were performed using patient’s whole blood with type 1 VWD, mixed with rVWF (Vonvendi®; 1.6 IU/mL), rFVIII or peg-EHL-rFVIII (Advate® or Adynovate®; 1.0 IU/mL), or both. Similar experiments were also conducted with clinical medical devices (T-TAS®). Results The addition of rFVIII did not augment thrombus formation assessed by surface coverage (SC) and thrombus height (TH), whereas rVWF enhanced these parameters (SC 19.1 ± 1.1% vs. 30.1 ± 4.1%, TH 2.2 ± 0.14 μm vs. 3.6 ± 0.40 μm, respectively). The co-presence of rVWF/rFVIII was comparable to plasma-derived VWF/FVIII (Confact®, VWF:FVIII ratio = 1.6:1.0) for increasing thrombogenicity in SC (32.5 ± 4.3% vs. 38.7 ± 5.5%) and in TH (5.0 ± 0.60 μm vs. 5.5 ± 0.64 μm), respectively. The pre-incubation time with rVWF and rFVIII appeared to have a little effect on the size of thrombus. Peg-EHL-rFVIII mediated thrombus formation to similar extent as rFVIII in the co-presence of rVWF. Similar results were obtained even with T-TAS. Immunostaining demonstrated that rFVIII and peg-EHL-rFVIII were similarly co-localized with rVWF in formed thrombi, indicating that pegylation did not interfere with molecular complexes. Conclusion The effects of high-level rVWF and peg-EHL-rFVIII on thrombus formation were comparable to conventional therapeutic products in a patient’s whole blood with VWD under high shear flow.